2021
DOI: 10.3390/medicina57030223
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Stress Fractures in Sport: Preventive and Therapeutic Measures—A Narrative Review

Abstract: There are numerous risk factors for stress fractures that have been identified in literature. Among different risk factors, a prolonged lack of vitamin D (25(OH)D) can lead to stress fractures in athletes since 25(OH)D insufficiency is associated with an increased incidence of a fracture. A 25(OH)D value of <75.8 nmol/L is a risk factor for a stress fracture. 25(OH)D deficiency is, however, only one of several potential risk factors. Well-documented risk factors for a stress fracture include female sex, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 170 publications
0
42
0
11
Order By: Relevance
“…Furthermore, it suggested that inadequate vitamin D levels could increase the risk of hamstring injuries. Particularly, vitamin D deficiency has been demonstrated to increase the incidence of stress fractures among musculoskeletal injuries in athletes [ 43 - 45 ]. Knechtle et al [ 43 ] reported that vitamin D deficiency was a risk factor for stress fractures in athletes.…”
Section: Vitamin D and Musculoskeletal Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it suggested that inadequate vitamin D levels could increase the risk of hamstring injuries. Particularly, vitamin D deficiency has been demonstrated to increase the incidence of stress fractures among musculoskeletal injuries in athletes [ 43 - 45 ]. Knechtle et al [ 43 ] reported that vitamin D deficiency was a risk factor for stress fractures in athletes.…”
Section: Vitamin D and Musculoskeletal Injuriesmentioning
confidence: 99%
“…Particularly, vitamin D deficiency has been demonstrated to increase the incidence of stress fractures among musculoskeletal injuries in athletes [ 43 - 45 ]. Knechtle et al [ 43 ] reported that vitamin D deficiency was a risk factor for stress fractures in athletes. Shimasaki et al [ 45 ] demonstrated that fifth metatarsal stress fractures were 5.1 and 2.9 times higher in athletes with 25(OH)D levels of 10 and 20 ng/mL, respectively.…”
Section: Vitamin D and Musculoskeletal Injuriesmentioning
confidence: 99%
“…Stress fractures are particularly a common type of bone injury, which occurs either as a result of excessive stress on the bone, 1 exceeding the bone's capacity to withstand and heal from those forces, 2 or as insufficiency fractures due to secondary osteoporosis. 1 Such fractures act as a source of significant morbidity in physically active people, from recreational exercisers to military recruits. 1,2 The paramilitary trainee represents a unique population exposed to intense physical stress, 3 characterized by excessive stress on the bone.…”
Section: Introductionmentioning
confidence: 99%
“…1 Such fractures act as a source of significant morbidity in physically active people, from recreational exercisers to military recruits. 1,2 The paramilitary trainee represents a unique population exposed to intense physical stress, 3 characterized by excessive stress on the bone. 1 Energy deficits, due to restrictive dietary patterns, in such personnel may reduce the muscle mass and bone strength needed for optimal performance, which makes them more susceptible to developing stress fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, vitamin D affects the regulation of the differentiation, proliferation, and growth of cells; hormone production; and immune, nervous, and muscle systems [ 7 ]. Regarding these functions, vitamin D is considered to play a role in optimal sports performance since it is involved in muscle physiology as muscles express a high number of vitamin D receptors, affects the transport of phosphate and calcium across muscle cell membranes, modulates phospholipid metabolism, and induces the expression of several myogenic transcription factors and myotubular sizes, which together affect the contractile filaments [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%